Road conectivity and illicit economies in the peruvian Amazon - Salazar Valdivia, Ciro Abelardo (2022)
In the last five decades, the expansion of road connectivity in Peru, particularly in its Amazon region, has contributed to the growth of illicit economies. This relationship, however, has been little studied and therefore has not been incorporated into the framework of public policies with the aim of avoiding or reducing its occurrence. This research seeks to expose what conditions have made this relationship possible in the Peruvian Amazon and what are the current risks that this region faces, taking into account that if the road initiatives currently planned in this region are executed, its stock of roads would increase fivefold in the present decade. A set of criteria is proposed with the aim of avoiding initiatives that can be considered high risk as well as actions to mitigate the growth of illicit economies in the areas of influence of new road projects.